Mid-term outcomes after percutaneous interventions in coronary bifurcations - Zimarino, Marco; Briguori, Carlo; Amat-Santos, Ignacio J; Radico, Francesco; Barbato, Emanuele; Chieffo, Alaide; Cirillo, Plinio; Costa, Ricardo A; Erglis, Andrejs; Gamra, Habib; Gil, Robert J; Kanic, Vojko; et al. (Elsevier BV, 2019)
The optimal treatment of patients undergoing percutaneous coronary interventions (PCI) for lesions located at coronary bifurcations is still debated.